Perioperative approach of patient with takotsubo syndrome - Barros,Joana (2017)
Abstract Introduction: Takotsubo cardiomyopathy (TCM) is a stress-induced cardiomyopathy. It is characterized by an acute onset of symptoms and electrocardiographic abnormalities mimicking an acute coronary syndrome in the absence of obstructive coronary artery disease. Any anesthetic-surgical event corresponds to a stressful situation, so the anesthetic management of patients with TCM requires special care throughout the perioperative period. We describe the anesthetic management of a patient with a confirmed diagnosis of TCM undergoing segmental colectomy. Case report: Female patient, 55 years old, ASA III, with history of takotsubo syndrome diagnosed 2 years ago, scheduled for segmental colectomy. The patient, without other changes in preoperative evaluation, underwent general anesthesia associated with lumbar epidural and remained hemodynamically stable during the 2 h of surgery. After a brief stay in the Post-Anesthesia Care Unit, she was transferred to the Intermediate Care Unit (IMCU), with epidural analgesia for postoperative period. Conclusion: TCM is a rare disease which true pathophysiology remains unclear, as well as the most appropriate anesthetic-surgical strategy. In this case, through a preventive approach, with close monitoring and the lowest possible stimulus, all the perioperative period was uneventful. Because it is a rare disease, this report could help to raise awareness about TCM.